CO2 offsetting companies as consumer responsibility innovation - Katarzyna Negacz; Anna Para (Economic and Environmental Studies (E&ES), 2014)
The aim of this paper is to examine the role of CO2 offsetting enterprises in pursuing the concept of sustainable development. The authors analyze business model, innovative potential and the impact of these companies on the consumers. Research methods used in the paper are the literature analysis and case study. Within the past years the concept of sustainable development has been gradually applied in the companies in numerous sectors. Simultaneously, consumers become increasingly more aware of their impact on the natural environment. As a result, first companies were established which enable to off-set amount of CO2 produced at various stages of manufacturing and delivering services. Thanks to them, a responsible consumer may contribute to the projects which help to reduce greenhouse gas emissions by donating chosen amount of money. The authors consider companies' attitudes related to the operations of these companies.
Keywords: 330; CO2 offsetting; sustainability; CSR; innovation